A self-powered polarized light detector based on b-hfte5 / tmd / t-hfte5 double heterojunction and a preparation method and application thereof
Patent Information
- Application Number
- CN202611023347.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-09-29
- Estimated Expiration
- 2046-07-10
AI Technical Summary
[0006]本发明的目的在于,提供一种基于B-HfTe5/TMD/T-HfTe5双异质结的自供能偏振光探测器及其制备方法和应用,以解决现有偏振光探测器依赖外部偏振元件、集成复杂、暗电流较高、偏振响应不足和难以自供能工作的问题
本发明采用B-HfTe5/TMD/T-HfTe5双异质结结构,利用上下两个HfTe5/TMD异质界面形成双内建电场,可在零偏压下实现光生载流子的高效分离与收集,从而实现自供能光电探测。TMD层被夹设于两层HfTe5之间,使TMD层处于完全耗尽或近耗尽状态,这有效降低了器件的暗电流,提高了探测灵敏度和弱光响应能力。同时,本发明利用HfTe5的面内各向异性吸收特性,使顶层HfTe5纳米片作为偏振选择或偏振调制功能层,从而使器件输出光电流随入射光偏振角发生周期性变化,赋予器件偏振敏感光探测能力。
Smart Images

Figure CN122534981B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of photoelectric detection and polarization imaging technology of two-dimensional materials, and in particular to a self-powered polarization detector based on B-HfTe5 / TMD / T-HfTe5 double heterojunction, its fabrication method and application. Background Technology
[0002] Photodetectors convert optical signals into electrical signals and have important applications in optical communication, machine vision, image sensing, health monitoring, environmental recognition, and intelligent sensing. Traditional commercial photodetectors are mainly based on semiconductor materials such as Si, Ge, InGaAs, and HgCdTe. Although they have a relatively mature manufacturing process, they still have certain limitations in terms of device miniaturization, on-chip integration, multi-dimensional optical information acquisition, and low-power operation.
[0003] On the other hand, polarization is one of the important degrees of freedom of light. Compared with ordinary light intensity detection, polarization detection can provide additional information such as the surface texture, material anisotropy, scattering characteristics, and geometry of the target object, which is of great value in fields such as machine vision, remote sensing imaging, biomedical imaging, defect detection, and encrypted information identification. However, traditional polarization detection schemes usually require the integration of polarizers, beam splitters, micro / nano polarization arrays, or other external optical components with ordinary photodetectors, resulting in increased system size, complex fabrication processes, increased optical loss, and limiting their application in highly integrated on-chip systems.
[0004] In recent years, two-dimensional layered materials have attracted widespread attention due to their strong light-matter interactions, atomic-level thickness, flexible integration capabilities, and rich band structures. Among them, two-dimensional materials with low-symmetry crystal structures can exhibit significant in-plane anisotropic absorption or anisotropic transport characteristics, providing a new material basis for constructing on-chip polarization-sensitive photodetectors. However, polarization detectors made of single two-dimensional materials typically face problems such as insufficient light absorption, high dark current, limited carrier separation efficiency, and insufficient self-powering capability.
[0005] Heterojunction structures can utilize the Fermi level difference between different materials to create a built-in electric field, thereby promoting the separation of photogenerated electrons and holes and achieving self-powered photoelectric detection. However, conventional single heterojunctions have limited depletion regions, making it difficult to simultaneously achieve low dark current, high sensitivity, fast response, and strong polarization selectivity. Therefore, designing a novel two-dimensional material heterojunction structure that combines a strong built-in electric field, low dark current, significant polarization selectivity, and efficient carrier separation capability has important scientific significance and application value. Summary of the Invention
[0006] The purpose of this invention is to provide a self-powered polarization photodetector based on a B-HfTe5 / TMD / T-HfTe5 double heterojunction, its fabrication method, and its applications, to solve the problems of existing polarization photodetectors, such as reliance on external polarization elements, complex integration, high dark current, insufficient polarization response, and difficulty in self-powered operation. This invention utilizes the two HfTe5 / TMD heterojunction interfaces to form a dual built-in electric field, enabling efficient separation and collection of photogenerated carriers under zero bias, thereby achieving self-powered photoelectric detection.
[0007] To achieve the above objectives, the present invention provides the following technical solution: One of the technical solutions of the present invention is to provide a self-powered polarization detector based on a B-HfTe5 / TMD / T-HfTe5 double heterojunction, wherein the self-powered polarization detector comprises, in a stacked manner, a silicon substrate, a B-HfTe5 layer, a TMD layer (two-dimensional light absorption layer) and a T-HfTe5 layer arranged sequentially. The TMD layer, serving as a light absorption layer, is sandwiched between the B-HfTe5 layer and the T-HfTe5 layer, forming a B-HfTe5 / TMD / T-HfTe5 dual heterojunction structure.
[0008] The B-HfTe5 layer and the T-HfTe5 layer respectively form a built-in electric field with the TMD layer, which is used to enable the TMD layer to generate photogenerated carrier separation under zero bias voltage and output photoelectric signals related to the polarization angle of the incident light. The T-HfTe5 layer is located on the incident light side and uses its in-plane anisotropic absorption to perform polarization selection or polarization modulation of the incident light; the B-HfTe5 layer is used to form a bottom heterojunction with the TMD layer and is used to reflect, scatter or modulate the light transmitted through the TMD layer to enhance the effective light absorption of the TMD layer.
[0009] Preferably, the material of the TMD layer is tungsten disulfide (WS2), tungsten diselenide (WSe2), molybdenum disulfide (MoS2), or molybdenum diselenide (MoSe2).
[0010] Preferably, the thickness of the B-HfTe5 layer is 40-200 nm, the width is 1-10 μm, and the length is 30-100 μm; The TMD layer has a thickness of 40-100 nm, a width of 1-50 μm, and a length of 30-200 μm; The thickness of the T-HfTe5 layer is 40-300 nm, the width is 1-10 μm, and the length is 30-200 μm.
[0011] Preferably, the self-powered polarization detector further includes a first electrode and a second electrode for outputting photocurrent signals.
[0012] Preferably, the alloy composition of the first electrode and the second electrode includes at least one of Au, Cr, Ag, Ti, Ni, Pd and Pt.
[0013] Preferably, the silicon substrate is a Si / SiO2 substrate.
[0014] The second technical solution of the present invention provides a method for fabricating the above-mentioned self-powered polarization detector based on B-HfTe5 / TMD / T-HfTe5 double heterojunction, comprising the following steps: B-HfTe5, TMD, and T-HfTe5 materials are sequentially stacked onto a silicon substrate using mechanical exfoliation and dry transfer to form a silicon substrate with a B-HfTe5 / TMD / T-HfTe5 dual heterojunction structure.
[0015] Preferably, the dry transfer includes achieving precise interface stacking using polyvinyl alcohol as a medium.
[0016] Preferably, after forming the silicon substrate with the B-HfTe5 / TMD / T-HfTe5 double heterojunction structure, the method further includes the following steps: Electrode patterns are fabricated on the silicon substrate having a B-HfTe5 / TMD / T-HfTe5 double heterojunction structure by photolithography and development. Then, metal is deposited on the electrode patterns to form electrodes, and the substrate is annealed to obtain the self-powered polarization detector.
[0017] Preferably, the method for preparing the electrode pattern includes the following steps: spin coating of photoresist using a spin coater, followed by heat treatment, exposure, and development to obtain the electrode pattern; The heat treatment is performed by heating on a hot table at 95-110℃ for 3-6 minutes. The exposure parameters are: the scanning speed of the lithography machine is 0.06-0.9 mm / s, the power is 6-28 mW, the light source is 375 nm ultraviolet laser, and the lithography is maskless; The development parameters include: the developer is a 3-7 wt% tetramethylammonium hydroxide aqueous solution, and the development time is 16-32 s; The spin coating process consists of two stages: the first stage has a speed of 500 rpm, an acceleration of 250 rpm / s, and a time of 5 s; the second stage has a speed of 4000 rpm, an acceleration of 2500 rpm / s, and a time of 55 s.
[0018] Preferably, the annealing temperature is 100-200℃, the atmosphere is an Ar / N2 mixed atmosphere, and the time is 25-120 min.
[0019] The third technical solution of the present invention provides an application of the above-mentioned self-powered polarization detector based on B-HfTe5 / TMD / T-HfTe5 double heterojunction in the field of integrated optoelectronic devices.
[0020] The fourth technical solution of the present invention provides a polarization light detection method, which uses the above-mentioned self-powered polarization light detector based on B-HfTe5 / TMD / T-HfTe5 double heterojunction to receive incident light, collects photocurrent signals under zero bias or low bias, and determines the polarization direction, polarization intensity or polarization state of the incident light based on the change of the photocurrent signal with the polarization angle of the incident light. The polarization angle of the incident light forms an angle with the crystal orientation of the HfTe5 nanosheets. θ Photocurrent signal follows θ It exhibits periodic changes.
[0021] The fifth technical solution of the present invention provides a polarization imaging system, including the above-mentioned self-powered polarization light detector based on B-HfTe5 / TMD / T-HfTe5 double heterojunction, light source, polarization modulation module, scanning module and signal acquisition module; The signal acquisition module is used to acquire the photocurrent signal of the self-powered polarization detector at different spatial positions and / or different polarization angles, and reconstruct the light intensity image, polarization image or linear polarization degree image of the target object; The light source is used to emit a stable illumination beam to illuminate the target object and provide the light energy required for polarization imaging. The polarization modulation module is used to control the polarization state of the beam incident on the target object to generate linearly polarized light with different polarization angles, so as to realize multi-angle polarization measurement. The scanning module is used to change the relative position of the illumination beam and the target object to achieve point-by-point scanning of the two-dimensional spatial region of the target object, thereby obtaining the light response signal at different spatial positions.
[0022] The technical principle of this invention is as follows: HfTe5 is a layered material with a low-symmetry crystal structure. Its in-plane orientation-dependent optical and electrical properties make it suitable as the polarization-sensitive functional layer in the system of this invention. Two-dimensional transition metal chalcogenide (TMD) materials have good light absorption and semiconductor properties, making them suitable as the light absorption layer in the system of this invention. After sandwiching the TMD layer between the top HfTe5 (T-HfTe5) and the bottom HfTe5 (B-HfTe5), the anisotropic absorption within the top T-HfTe5 layer can be used to polarize the incident light, allowing the intermediate TMD layer to absorb light anisotropically. Simultaneously, the HfTe5 / TMD dual heterojunction allows the intermediate TMD layer to be completely depleted, forming a large built-in electric field to rapidly separate photogenerated carriers, achieving self-powered, high-performance polarization-sensitive photodetector.
[0023] The beneficial technical effects of the present invention are as follows: This invention employs a B-HfTe5 / TMD / T-HfTe5 dual heterojunction structure, utilizing the two HfTe5 / TMD heterojunction interfaces to form a dual built-in electric field. This enables efficient separation and collection of photogenerated carriers under zero bias, thereby achieving self-powered photodetection. The TMD layer is sandwiched between the two HfTe5 layers, placing the TMD layer in a fully depleted or near-depleted state. This effectively reduces the device's dark current and improves detection sensitivity and weak light response. Simultaneously, this invention utilizes the in-plane anisotropic absorption characteristics of HfTe5, allowing the top HfTe5 nanosheet to function as a polarization selection or polarization modulation layer. This causes the device's output photocurrent to periodically change with the incident light polarization angle, endowing the device with polarization-sensitive light detection capabilities.
[0024] The TMD layer in this invention can be made of a variety of two-dimensional materials, indicating that this invention has good material versatility and can flexibly select the light absorption layer according to the target detection band and device performance requirements.
[0025] Based on the above characteristics, the self-powered polarization detector of the present invention can be used for polarization angle identification, low-light imaging, polarization imaging and linear polarization degree detection, and has broad application prospects in machine vision, surface texture recognition, defect detection, information encryption recognition and integrated optoelectronic sensing systems. Attached Figure Description
[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0027] Figure 1This is a schematic diagram of the structure of the self-powered polarization detector based on the B-HfTe5 / WS2 / T-HfTe5 double heterojunction in Example 1.
[0028] Figure 2 This is a schematic diagram of the internal depletion region of the self-powered polarization detector based on the B-HfTe5 / TMD / T-HfTe5 double heterojunction of the present invention.
[0029] Figure 3 This document describes the structural and photoelectric performance characterization of a self-powered polarization detector based on a B-HfTe5 / WS2 / T-HfTe5 double heterojunction as described in Example 1. (a) is an optical microscope image of the fabricated device; (b) are Raman spectra recorded from the individual WS2 region, B-HfTe5 / T-HfTe5 region, and B-HfTe5 / WS2 / T-HfTe5 region; (c) are IV characteristic curves under 405 nm illumination at different optical power densities; and (d) V... ds Time-resolved optical response diagram of 405 nm illumination at 0 V as illumination intensity increases.
[0030] Figure 4 The image shows the polarization photoelectric response of the self-powered polarization detector based on the B-HfTe5 / WS2 / T-HfTe5 double heterojunction in Example 1. (a) is a schematic diagram of the polarization-resolved photoresponse measurement device, (b) is the self-powered time-resolved photocurrent at different polarization angles under 635 nm illumination, and (c) is a polar coordinate graph showing the relationship between photocurrent and polarization angle.
[0031] Figure 5 The structure and photoelectric performance of the self-powered polarization detector based on the B-HfTe5 / WSe2 / T-HfTe5 double heterojunction prepared in Example 5 are characterized. (a) is an optical microscope image of the fabricated device, (b) is the IV characteristics under 405 nm illumination at different optical power densities, (c) is the self-powered time-resolved photocurrent at different polarization angles under 405 nm illumination, and (d) is a polar coordinate graph of the relationship between photocurrent and polarization angle.
[0032] Figure 6 The following is a structural and photoelectric performance characterization of the self-powered polarization detector based on the B-HfTe5 / MoS2 / T-HfTe5 double heterojunction in Example 6. (a) is an optical microscope image of the fabricated device, (b) is the IV characteristics under 405 nm illumination at different optical power densities, (c) is the self-powered time-resolved photocurrent at different polarization angles under 405 nm illumination, and (d) is a polar coordinate plot of the relationship between photocurrent and polarization angle.
[0033] Figure 7The structure and photoelectric performance of the self-powered polarization detector based on the B-HfTe5 / MoSe2 / T-HfTe5 double heterojunction in Example 7 are characterized. (a) is an optical microscope image of the fabricated device, (b) is the IV characteristics under 405 nm illumination at different optical power densities, (c) is the self-powered time-resolved photocurrent at different polarization angles under 405 nm illumination, and (d) is a polar coordinate graph showing the relationship between photocurrent and polarization angle.
[0034] Figure 8 The images shown are simulated polarization images at different angles (0°, 30°, 60°, 90°) of the imaging system based on the B-HfTe5 / WS2 / T-HfTe5 double heterojunction self-powered polarization detector in Example 4.
[0035] Figure 9 The structure and polarization photoelectric performance of the self-powered polarization photodetector based on the B-HfTe5 / WS2 heterojunction are shown in Comparative Example 1. (a) is an optical microscope image of the fabricated device, (b) is the self-powered time-resolved photocurrent at different polarization angles under 405 nm illumination, and (c) is a polar coordinate plot of the relationship between photocurrent and polarization angle.
[0036] Figure 10 The structure and polarization photoelectric performance of the self-powered polarized light detector based on the T-HfTe5 / WS2 heterojunction are shown in Comparative Example 2. (a) is an optical microscope image of the fabricated device, (b) is the self-powered time-resolved photocurrent at different polarization angles under 405 nm illumination, and (c) is a polar coordinate graph showing the relationship between photocurrent and polarization angle.
[0037] Figure 11 This document compares the performance of the self-powered polarization detector based on the B-HfTe5 / WS2 / T-HfTe5 double heterojunction in Example 1 with the self-powered polarization detector based on the B-HfTe5 / WS2 heterojunction in Comparative Example 1 and the self-powered polarization detector based on the T-HfTe5 / WS2 heterojunction in Comparative Example 2. In Example 1, (a) is a comparison of responsivity (R) and specific detectivity (D*), and in Example 2, (b) is a comparison of polarization anisotropy ratio (AR).
[0038] Figure 12The figures show an AR comparison of the self-powered polarization detector based on a B-HfTe5 / WS2 / T-HfTe5 double heterojunction in Example 1, the self-powered polarization detector based on a B-HfTe5 / WSe2 / T-HfTe5 double heterojunction in Example 5, the self-powered polarization detector based on a B-HfTe5 / MoS2 / T-HfTe5 double heterojunction in Example 6, and the self-powered polarization detector based on a B-HfTe5 / MoSe2 / T-HfTe5 double heterojunction in Example 7, with the corresponding mirror-image structure devices of Comparative Examples 3-6. As can be seen from the figures, the outer HfTe5 layer exhibits a stronger polarization anisotropy ratio than the inner layer.
[0039] Figure 13 The data on polarization response obtained by in-situ testing of WS2 in the self-powered polarization detector based on B-HfTe5 / WS2 / T-HfTe5 double heterojunction in Example 1 are shown in (a) and (b) respectively. (a) shows the self-powered time-resolved photocurrent at different polarization angles under 405 nm illumination.
[0040] Figure 14 This is a performance comparison chart of the self-powered polarization detector based on the B-HfTe5 / WS2 / T-HfTe5 double heterojunction in Example 1 and the WSe2 / Ta2NiSe3 / WSe2 in the prior art. Detailed Implementation
[0041] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.
[0042] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, are also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0043] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. It should be noted that any aspects of this invention not described in detail are conventional practices in the art and are not the focus of this invention.
[0044] The terms “comprising,” “including,” “having,” “containing,” etc., used in this invention are all open-ended terms, meaning that they include but are not limited to.
[0045] This invention provides a method for fabricating a self-powered polarization detector based on a B-HfTe5 / TMD / T-HfTe5 double heterojunction, comprising the following steps: S1. Remove B-HfTe5 material using mechanical peeling method: Using B-HfTe5 single crystal as raw material, use low-adhesion blue film tape to repeatedly peel (3-5 times) the single crystal and stick it on SiO2 / Si substrate to obtain SiO2 / Si substrate with B-HfTe5 layer. The thickness of the B-HfTe5 layer is 40-200 nm, the width is 1-10 μm, and the length is 30-100 μm; S2. PVA (polyvinyl alcohol) solution (concentration of 4wt%) is dropped onto a polydimethylsiloxane (PDMS) film that can cover the material. The film is then gently scraped flat with a glass slide and dried at 55°C for 10 min to obtain a cured PVA film. The film is then placed on a clean glass slide. S3. TMD is removed by mechanical peeling: Using TMD single crystal as raw material, the single crystal is repeatedly peeled (3-5 times) with low-tack blue film tape and adhered to the PVA film to obtain a PVA film with TMD layer. The thickness of the TMD layer is 40-100 nm, the width is 1-50 μm, and the length is 30-200 μm; S4. Place the SiO2 / Si substrate with the B-HfTe5 layer on the sample stage of the transfer stage, fix the PVA film with the TMD layer in the slot of the transfer stage, observe the overlapping part through the microscope of the transfer stage, select a suitable junction area, and gradually attach the two by controlling the transfer platform. Heat at 90-95℃ for 3-4 min, then remove and soak in 55℃ deionized water for 15-30 min. After removal, remove the PVA film on the surface, blow off the solvent with nitrogen gas and dry to obtain the SiO2 / Si substrate with B-HfTe5 / TMD van der Waals heterojunction. The B-HfTe5 layer and the TMD layer are not completely overlapped, but have a misaligned structure. The areas of both layers other than the overlapping parts are exposed for at least 5-10 μm in length in order to complete the subsequent electrode fabrication. The exposed area of the TMD layer is referred to as the TMD region. S5. Add PVA solution (concentration of 4wt%) to a polydimethylsiloxane (PDMS) film that can cover the material, scrape it flat with a glass slide, dry it at 55°C for 10 min to obtain a cured PVA film, and place it on a clean glass slide. S6. T-HfTe5 is removed by mechanical peeling: Using T-HfTe5 single crystal as raw material, the single crystal is repeatedly peeled (3-5 times) with low-adhesion blue film tape and adhered to the PVA film to obtain a PVA film with T-HfTe5 layer. The thickness of the T-HfTe5 layer is 40-300 nm, the width is 1-10 μm, and the length is 30-200 μm; S7. Place the SiO2 / Si substrate with B-HfTe5 / TMD van der Waals heterojunction on the sample stage of the transfer stage. Fix the PVA film with T-HfTe5 layer in the slot of the transfer stage. Observe the overlapping part through the microscope of the transfer stage, select a suitable junction area, and gradually attach the two by controlling the transfer platform. Heat at 90-95℃ for 3-4 min, then remove and soak in 55℃ deionized water for 15-30 min. After removal, remove the PVA film on the surface, blow off the solvent with nitrogen gas and dry to obtain the SiO2 / Si substrate with B-HfTe5 / TMD / T-HfTe5 van der Waals heterojunction. The T-HfTe5 layer and the B-HfTe5 layer are stacked in such a way that the substrates completely overlap. The exposed areas of the B-HfTe5 layer and the exposed areas of the T-HfTe5 layer have the same length in the vertical direction. Due to the van der Waals forces between the two layers, which are similar to the structural forces between intrinsic layers of the material, even if the B-HfTe5 layer is not exposed, it can still be regarded as a whole. The region where the B-HfTe5 layer, TMD layer, and T-HfTe5 layer overlap is denoted as the B-HfTe5 / TMD / T-HfTe5 region; the region where the B-HfTe5 layer and T-HfTe5 layer overlap is denoted as the B-HfTe5 / T-HfTe5 region. S8. A spin coater is used to spin-coat the SiO2 / Si substrate with the B-HfTe5 / TMD / T-HfTe5 van der Waals heterojunction. Then, the substrate is heated at 95-110℃ for 3-6 min. Electron beam lithography is then used to precisely position and expose the electrode pattern. The exposed heterojunction is then developed with a developer, fixed with deionized water, and dried after the solvent is removed by a nitrogen stream to obtain the photolithographic heterojunction. The exposure and development parameters are as follows: the scanning speed of the lithography machine is 0.06-0.9 mm / s, the power is 6-28 mW, the developer is a 3-7 wt% tetramethylammonium hydroxide aqueous solution, and the development time is 16-32 s. S9. Metal is deposited on the photolithographically etched heterojunction to form drain and source electrodes, with part of the source electrode located on the surface of the T-HfTe5 / B-HfTe5 region and the other part on the surface of the SiO2 / Si substrate, and part of the drain electrode located on the surface of the TMD region and the other part on the surface of the SiO2 / Si substrate. After the deposition is completed, the photoresist is removed with acetone solution, the solvent is blown off by nitrogen gas and dried, and finally vacuum high-temperature annealing is performed. The conditions for the high-temperature annealing are: annealing temperature of 100-200℃, atmosphere of Ar / N2 mixed gas, and annealing time of 25-120 min, to obtain a self-powered polarization detector based on B-HfTe5 / TMD / T-HfTe5 double heterojunction; wherein the type of deposited metal is at least one of Au, Cr, Ag, Ti, Ni, Pd and Pt.
[0046] In the self-powered polarization detector based on the B-HfTe5 / TMD / T-HfTe5 double heterojunction, the top HfTe5 layer utilizes its significant in-plane lattice anisotropy to polarize the incident light to a fixed angle through anisotropic optical absorption, acting as a nanoscale polarizer; the middle TMD layer serves as the main light absorption layer, absorbing the polarized light and generating a large number of photogenerated carriers; the bottom HfTe5 layer reflects part of the light transmitted through the TMD layer back to the TMD layer to achieve secondary absorption, significantly enhancing the light response. Two HfTe5 / TMD heterojunctions form a dual built-in electric field synergistic mechanism: under zero bias (self-powered) conditions, the dual built-in electric fields provide the driving force for the directional migration of photogenerated electron-hole pairs, effectively confining electrons within the TMD layer and rapidly migrating holes to the HfTe5 layers on both sides. Simultaneously, the TMD layer is in a fully depleted or near-depleted state, greatly suppressing dark current and significantly improving photoresponse speed, photoresponsivity, detectivity, and weak light detection capability. Combined with its polarization-sensitive characteristics, high-resolution polarization imaging and linear polarization degree detection can be achieved. Compared to conventional schemes that place anisotropic materials between two light-absorbing materials, the scheme employed in this invention effectively depletes the intermediate light-absorbing material completely, generating a large built-in electric field that rapidly separates photogenerated carriers, improving the device's photoelectric response performance.
[0047] The self-powered polarization detector based on a B-HfTe5 / TMD / T-HfTe5 dual heterojunction provided by this invention has the core highlight of integrating excellent self-driven photoelectric detection performance and high-sensitivity polarization detection function into a single van der Waals heterojunction device. On the one hand, the zero-bias operating mode completely eliminates the dependence of traditional detectors on external bias sources, fundamentally solving the problems of high power consumption and complex structure, and adapting to the low-power requirements of portable and wearable devices. On the other hand, the intrinsic polarization detection capability avoids the problems of increased system size, cost, and signal loss caused by additional optical components, significantly improving the functional integration of the device. This design shows broad application prospects in miniaturized optoelectronic devices, integrated optical systems, quantum information processing, remote sensing, and other fields, providing a new technical path for the development of low-power, multifunctional optical detection technology.
[0048] Unless otherwise specified, all raw materials and reagents involved in the specific embodiments of this invention are commercially available products.
[0049] Unless otherwise specified, room temperature and normal temperature in the specific embodiments of this invention refer to 20-30℃.
[0050] Unless otherwise specified, all percentages mentioned in the specific embodiments of this invention refer to mass percentages.
[0051] The SiO2 / Si substrates used in the specific embodiments of the present invention were all pretreated before use, as follows: ultrasonically cleaned in acetone, ethanol and deionized water for 15 min in sequence, and dried after the solvent was blown off by nitrogen flow.
[0052] The B-HfTe5 single crystal, T-HfTe5 single crystal, and HfTe5 single crystal used in the specific embodiments of the present invention are all of the same type of material and are prepared by chemical vapor deposition.
[0053] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.
[0054] The technical solution of the present invention will be further illustrated by the following embodiments.
[0055] Example 1 Fabrication of a self-powered polarization detector based on a B-HfTe5 / WS2 / T-HfTe5 double heterojunction: S1. Remove B-HfTe5 material by mechanical peeling: Using B-HfTe5 single crystal as raw material, the single crystal is repeatedly peeled (5 times) with low-viscosity blue film tape and attached to SiO2 / Si substrate to obtain SiO2 / Si substrate with B-HfTe5 layer. The B-HfTe5 layer has a thickness of 119 nm, a width of 3 μm, and a length of 60 μm; S2. PVA solution (concentration of 4wt%) is dropped onto a polydimethylsiloxane (PDMS) film that can cover the material. The film is then gently scraped flat with a glass slide and dried at 55°C for 10 min to obtain a cured PVA film. The film is then placed on a clean glass slide. S3. Remove WS2 using mechanical peeling method: Using WS2 single crystal as raw material, repeatedly peel (3-5 times) the single crystal with low-tack blue film tape and stick it on the PVA film to obtain a PVA film with WS2 layer; The WS2 layer has a thickness of 45nm, a width of 18μm, and a length of 38μm; S4. Place the SiO2 / Si substrate with the B-HfTe5 layer on the sample stage of the transfer stage, fix the PVA film with the WS2 layer in the slot of the transfer stage, observe the overlapping part through the microscope of the transfer stage, select a suitable junction area, and gradually attach the two by controlling the transfer platform. Heat at 95℃ for 3 min, then remove and soak in 55℃ deionized water for 15 min. After removal, remove the PVA film on the surface, blow off the solvent with nitrogen gas and dry to obtain the SiO2 / Si substrate with the B-HfTe5 / WS2 van der Waals heterojunction. The B-HfTe5 layer and the WS2 layer are not completely overlapped, but have a misaligned structure. The areas of the two layers other than the overlapping parts are exposed with lengths of 23μm and 32μm respectively. The exposed area of the WS2 layer is referred to as the WS2 region. S5. Add PVA solution (concentration of 4wt%) to a polydimethylsiloxane (PDMS) film that can cover the material, scrape it flat with a glass slide, dry it at 55°C for 10 min to obtain a cured PVA film, and place it on a clean glass slide. S6. T-HfTe5 is removed by mechanical peeling: Using T-HfTe5 single crystal as raw material, the single crystal is repeatedly peeled (5 times) with low-adhesion blue film tape and attached to the PVA film to obtain a PVA film with T-HfTe5 layer. The T-HfTe5 layer has a thickness of 209 nm, a width of 3 μm, and a length of 55 μm; S7. Place the SiO2 / Si substrate with B-HfTe5 / WS2 van der Waals heterojunction on the sample stage of the transfer stage. Fix the PVA film with T-HfTe5 layer in the slot of the transfer stage. Observe the overlapping part through the microscope of the transfer stage, select a suitable junction area, and gradually attach the two by controlling the transfer platform. Heat at 95℃ for 3 min, then remove and soak in 55℃ deionized water for 15 min. After removal, remove the PVA film on the surface, blow off the solvent with nitrogen gas and dry to obtain the SiO2 / Si substrate with B-HfTe5 / WS2 / T-HfTe5 van der Waals heterojunction. The T-HfTe5 layer and the B-HfTe5 layer are stacked in such a way that the substrates completely overlap. The exposed areas of the B-HfTe5 layer and the exposed areas of the T-HfTe5 layer have the same length in the vertical direction. Due to the van der Waals forces between the two layers, which are similar to the structural forces between intrinsic layers of the material, even if the B-HfTe5 layer is not exposed, it can still be regarded as a whole. The region where B-HfTe5, WS2, and T-HfTe5 layers overlap is denoted as the B-HfTe5 / WS2 / T-HfTe5 region; the region where B-HfTe5 and T-HfTe5 layers overlap is denoted as the B-HfTe5 / T-HfTe5 region. S8. A spin coater was used to spin-coat a SiO2 / Si substrate with a B-HfTe5 / WS2 / T-HfTe5 van der Waals heterojunction. The substrate was then heated at 105℃ for 4 min. Electron beam lithography was then used to precisely position and expose the electrode pattern. The exposed heterojunction was then developed with a developer, fixed with deionized water, and dried after the solvent was removed by a nitrogen stream to obtain the photolithographic heterojunction. The exposure and development parameters were as follows: the scanning speed of the lithography machine was 0.9 mm / s, the power was 28mW, the developer was a 6 wt% tetramethylammonium hydroxide aqueous solution, and the development time was 18 s. S9. Metal is deposited onto the heterojunction after photolithography to form drain and source electrodes. Simultaneously, part of the source electrode is located on the surface of the T-HfTe5 / B-HfTe5 region, and the other part is located on the surface of the SiO2 / Si substrate. Similarly, part of the drain electrode is located on the surface of the WS2 region, and the other part is located on the surface of the SiO2 / Si substrate (see...). Figure 1 After the evaporation is completed, the photoresist is removed with acetone solution, the solvent is blown off by nitrogen gas and then dried, and finally vacuum high-temperature annealing is performed. The conditions for high-temperature annealing are: annealing temperature of 150℃, atmosphere of Ar / N2 mixed gas, and annealing time of 50 min, to obtain a self-powered polarization detector based on B-HfTe5 / WS2 / T-HfTe5 double heterojunction.
[0056] Example 2 Self-Powered Photodetector Based on B-HfTe5 / WS2 / T-HfTe5 Double Heterojunction Photoelectric testing was performed on the self-powered polarization detector of the B-HfTe5 / WS2 / T-HfTe5 double heterojunction prepared in Example 1.
[0057] Under zero applied bias, incident light of different wavelengths is irradiated onto the device surface. The incident light first passes through the top layer HfTe5, where, due to the in-plane anisotropic absorption characteristics of HfTe5, the incident light is polarization-selective or polarization-modulated. Subsequently, the modulated light enters the intermediate WS2 light-absorbing layer, where photogenerated electron-hole pairs are generated.
[0058] Since the bottom HfTe5 and WS2 form a bottom heterojunction, and the top HfTe5 and WS2 form a top heterojunction, the two heterojunctions together generate a built-in electric field under zero bias. This built-in electric field drives the separation of photogenerated electrons and holes, and outputs a photocurrent signal through the electrodes. Therefore, this device can achieve self-powered photodetection without an external operating voltage.
[0059] In this embodiment, the device can respond to light in the ultraviolet to near-infrared bands, and in particular, it can achieve a significant self-powered photoelectric response in the visible light band. Due to the double heterojunction structure, the WS2 layer is in a depleted or near-depleted state, and the device has low dark current and a high photocurrent on / off ratio, which can be used for weak light detection and low-power photoelectric sensing.
[0060] Example 3 Polarization-sensitive photodetector based on a self-powered polarization detector of B-HfTe5 / WS2 / T-HfTe5 double heterojunction The polarization angle-dependent photoelectric response of the B-HfTe5 / WS2 / T-HfTe5 double heterojunction prepared in Example 1 was tested.
[0061] Linearly polarized light is irradiated onto the surface of the device, and the polarization angle of the incident light is changed. θ ,in θ The angle between the polarization direction of the incident light and the long axis of the HfTe5 nanosheet crystal is defined. Photocurrent signals from the device at different polarization angles are collected while keeping the incident light power essentially constant.
[0062] Test results show that the output photocurrent of the device varies periodically with the polarization angle of the incident light, exhibiting a significant polarization-sensitive response. This polarization-sensitive response originates from the in-plane anisotropic absorption of HfTe5 and the enhanced carrier separation effect of the B-HfTe5 / WS2 / T-HfTe5 double heterojunction structure.
[0063] In this embodiment, the photocurrent can satisfy the following angle dependence: in, I ph Photocurrent, I max For the maximum photocurrent, I min For the minimum photocurrent, θ The incident light polarization angle, φ This is the phase offset angle.
[0064] The polarization anisotropy ratio AR can be defined as: AR = I max / I min Therefore, the device can be used to identify the polarization direction, polarization intensity, or polarization state of incident light.
[0065] Example 4 Polarization Imaging Applications of Self-Powered Polarization Detectors Based on B-HfTe5 / WS2 / T-HfTe5 Double Heterojunctions The self-powered polarization detector of the B-HfTe5 / WS2 / T-HfTe5 double heterojunction prepared in Example 1 was used as a single-pixel detection unit for polarization imaging testing.
[0066] The polarization imaging system includes a light source, a polarization modulation module, a target under test, a scanning module, a B-HfTe5 / WS2 / T-HfTe5 self-powered polarization detector, and a signal acquisition module. Light emitted from the light source is modulated by the polarization modulation module before illuminating the target under test. The transmitted or reflected light then enters the B-HfTe5 / WS2 / T-HfTe5 detector. The scanning module is used to change the relative position between the target under test and the detector, and the signal acquisition module is used to record the photocurrent signal at different spatial positions.
[0067] Since the detector of the present invention can output a photocurrent signal related to the incident light intensity and polarization angle under zero bias, the light intensity image and polarization image of the target object can be reconstructed by spatial scanning.
[0068] Furthermore, by acquiring image signals at different polarization angles, the linear polarization degree image of the target object can be obtained.
[0069] This method can be used for object surface texture recognition, material anisotropy recognition, defect detection, low-light imaging, and information encryption recognition.
[0070] Example 5 Fabrication of a self-powered polarization detector based on a B-HfTe5 / WSe2 / T-HfTe5 double heterojunction: S1. Remove B-HfTe5 material by mechanical peeling: Using B-HfTe5 single crystal as raw material, the single crystal is repeatedly peeled (5 times) with low-viscosity blue film tape and attached to SiO2 / Si substrate to obtain SiO2 / Si substrate with B-HfTe5 layer. The B-HfTe5 layer has a thickness of 115 nm, a width of 3 μm, and a length of 79 μm; S2. PVA solution (concentration of 4wt%) is dropped onto a polydimethylsiloxane (PDMS) film that can cover the material. The film is then gently scraped flat with a glass slide and dried at 55°C for 10 min to obtain a cured PVA film. The film is then placed on a clean glass slide. S3. Using mechanical peeling method to peel off WSe2: Using WSe2 single crystal as raw material, the single crystal is repeatedly peeled (5 times) with low-adhesion blue film tape and attached to the PVA film to obtain a PVA film with WSe2 layer. The WSe2 layer has a thickness of 50 nm, a width of 18 μm, and a length of 23 μm; S4. Place the SiO2 / Si substrate with the B-HfTe5 layer on the sample stage of the transfer stage, fix the PVA film with the WSe2 layer in the slot of the transfer stage, observe the overlapping part through the microscope of the transfer stage, select a suitable junction area, and gradually attach the two by controlling the transfer platform. Heat at 95℃ for 3 min, then remove and soak in 55℃ deionized water for 15 min. After removal, remove the PVA film on the surface, blow off the solvent with nitrogen gas and dry to obtain the SiO2 / Si substrate with the B-HfTe5 / WSe2 van der Waals heterojunction. The B-HfTe5 layer and the WSe2 layer are not completely overlapped, but have a misaligned structure. The areas of the two layers other than the overlapping parts are exposed with lengths of 25 μm and 10 μm respectively. The exposed area of the WSe2 layer is referred to as the WSe2 region. S5. Add PVA solution (concentration of 4wt%) to a polydimethylsiloxane (PDMS) film that can cover the material, scrape it flat with a glass slide, dry it at 55°C for 10 min to obtain a cured PVA film, and place it on a clean glass slide. S6. T-HfTe5 is removed by mechanical peeling: Using T-HfTe5 single crystal as raw material, the single crystal is repeatedly peeled (5 times) with low-adhesion blue film tape and attached to the PVA film to obtain a PVA film with T-HfTe5 layer. The T-HfTe5 layer has a thickness of 202 nm, a width of 3.1 μm, and a length of 83 μm; S7. Place the SiO2 / Si substrate with B-HfTe5 / WSe2 van der Waals heterojunction on the sample stage of the transfer stage. Fix the PVA film with T-HfTe5 layer in the slot of the transfer stage. Observe the overlapping part through the microscope of the transfer stage, select a suitable junction area, and gradually attach the two by controlling the transfer platform. Heat at 95℃ for 3 min, then remove and soak in 55℃ deionized water for 15 min. After removal, remove the PVA film on the surface, blow off the solvent with nitrogen gas and dry to obtain the SiO2 / Si substrate with B-HfTe5 / WSe2 / T-HfTe5 van der Waals heterojunction. The T-HfTe5 layer and the B-HfTe5 layer are stacked in such a way that the substrates completely overlap. The exposed areas of the B-HfTe5 layer and the exposed areas of the T-HfTe5 layer have the same length in the vertical direction. Due to the van der Waals forces between the two layers, which are similar to the structural forces between intrinsic layers of the material, even if the B-HfTe5 layer is not exposed, it can still be regarded as a whole. The region where B-HfTe5, WSe2, and T-HfTe5 layers overlap is denoted as the B-HfTe5 / WSe2 / T-HfTe5 region; the region where B-HfTe5 and T-HfTe5 layers overlap is denoted as the B-HfTe5 / T-HfTe5 region. S8. A spin coater was used to spin-coat a SiO2 / Si substrate with a B-HfTe5 / WSe2 / T-HfTe5 van der Waals heterojunction. The substrate was then heated at 105℃ for 4 minutes. Electron beam lithography was then used to precisely position and expose the electrode pattern. The exposed heterojunction was then developed with a developer, fixed with deionized water, and dried after the solvent was removed by a nitrogen stream to obtain the photolithographic heterojunction. The exposure and development parameters were as follows: the scanning speed of the lithography machine was 0.9 mm / s, the power was 28mW, the developer was a 6 wt% tetramethylammonium hydroxide aqueous solution, and the development time was 18s. S9. Metal is deposited on the heterojunction after photolithography to form drain and source electrodes. Simultaneously, part of the source electrode is located on the surface of the T-HfTe5 / B-HfTe5 region, and the other part is located on the surface of the SiO2 / Si substrate. Similarly, part of the drain electrode is located on the surface of the WSe2 region, and the other part is located on the surface of the SiO2 / Si substrate. After the deposition is completed, the photoresist is removed with acetone solution, the solvent is blown off by nitrogen gas, and then the device is dried. Finally, it is subjected to vacuum high-temperature annealing. The conditions for high-temperature annealing are: annealing temperature of 150℃, atmosphere of Ar / N2 mixed gas, and annealing time of 50 min, to obtain a self-powered polarization detector based on the B-HfTe5 / WSe2 / T-HfTe5 double heterojunction.
[0071] Example 6 Fabrication of a self-powered polarization detector based on a B-HfTe5 / MoS2 / T-HfTe5 double heterojunction: S1. Remove B-HfTe5 material by mechanical peeling: Using B-HfTe5 single crystal as raw material, the single crystal is repeatedly peeled (5 times) with low-viscosity blue film tape and attached to SiO2 / Si substrate to obtain SiO2 / Si substrate with B-HfTe5 layer. The B-HfTe5 layer has a thickness of 125 nm, a width of 2 μm, and a length of 72 μm; S2. PVA solution (concentration of 4wt%) is dropped onto a polydimethylsiloxane (PDMS) film that can cover the material. The film is then gently scraped flat with a glass slide and dried at 55°C for 10 min to obtain a cured PVA film. The film is then placed on a clean glass slide. S3. MoS2 is removed by mechanical peeling: MoS2 single crystal is used as raw material, and the single crystal is repeatedly peeled (5 times) with low-adhesion blue film tape and attached to the PVA film to obtain a PVA film with a MoS2 layer. The MoS2 layer has a thickness of 50 nm, a width of 2 μm, and a length of 65 μm; S4. Place the SiO2 / Si substrate with the B-HfTe5 layer on the sample stage of the transfer stage, fix the PVA film with the MoS2 layer in the slot of the transfer stage, observe the overlapping part through the microscope of the transfer stage, select a suitable junction area, and gradually attach the two by controlling the transfer platform. Heat at 95℃ for 3 min, then remove and soak in 55℃ deionized water for 15 min. After removal, remove the PVA film on the surface, blow off the solvent with nitrogen gas and dry to obtain the SiO2 / Si substrate with the B-HfTe5 / MoS2 van der Waals heterojunction. The B-HfTe5 layer and the MoS2 layer are not completely overlapped, but have a misaligned structure. The areas of the two layers other than the overlapping parts are exposed with lengths of 31 μm and 20 μm, respectively. The exposed area of the MoS2 layer is referred to as the MoS2 region. S5. Add PVA solution (concentration of 4wt%) to a polydimethylsiloxane (PDMS) film that can cover the material, scrape it flat with a glass slide, dry it at 55°C for 10 min to obtain a cured PVA film, and place it on a clean glass slide. S6. T-HfTe5 is removed by mechanical peeling: Using T-HfTe5 single crystal as raw material, the single crystal is repeatedly peeled (5 times) with low-adhesion blue film tape and attached to the PVA film to obtain a PVA film with T-HfTe5 layer. The T-HfTe5 layer has a thickness of 198 nm, a width of 2 μm, and a length of 68 μm; S7. Place the SiO2 / Si substrate with B-HfTe5 / MoS2 van der Waals heterojunction on the sample stage of the transfer stage. Fix the PVA film with T-HfTe5 layer in the slot of the transfer stage. Observe the overlapping part through the microscope of the transfer stage, select a suitable junction area, and gradually attach the two by controlling the transfer platform. Heat at 95℃ for 3 min, then remove and soak in 55℃ deionized water for 15 min. After removal, remove the PVA film on the surface, blow off the solvent with nitrogen gas and dry to obtain the SiO2 / Si substrate with B-HfTe5 / MoS2 / T-HfTe5 van der Waals heterojunction. The T-HfTe5 layer and the B-HfTe5 layer are stacked in such a way that the substrates completely overlap. The exposed areas of the B-HfTe5 layer and the exposed areas of the T-HfTe5 layer have the same length in the vertical direction. Due to the van der Waals forces between the two layers, which are similar to the structural forces between intrinsic layers of the material, even if the B-HfTe5 layer is not exposed, it can still be regarded as a whole. The region where B-HfTe5, MoS2, and T-HfTe5 layers overlap is denoted as the B-HfTe5 / MoS2 / T-HfTe5 region; the region where B-HfTe5 and T-HfTe5 layers overlap is denoted as the B-HfTe5 / T-HfTe5 region. S8. A spin coater was used to spin-coat a SiO2 / Si substrate with a B-HfTe5 / MoS2 / T-HfTe5 van der Waals heterojunction. The substrate was then heated at 105℃ for 4 min. Electron beam lithography was then used to precisely position and expose the electrode pattern. The exposed heterojunction was then developed with a developer, fixed with deionized water, and dried after the solvent was removed by a nitrogen stream to obtain the photolithographic heterojunction. The exposure and development parameters were as follows: the scanning speed of the lithography machine was 0.9 mm / s, the power was 28mW, the developer was a 6 wt% tetramethylammonium hydroxide aqueous solution, and the development time was 18 s. S9. Metal is deposited on the heterojunction after photolithography to form drain and source electrodes. Simultaneously, part of the source electrode is located on the surface of the T-HfTe5 / B-HfTe5 region, and the other part is located on the surface of the SiO2 / Si substrate. Similarly, part of the drain electrode is located on the surface of the MoS2 region, and the other part is located on the surface of the SiO2 / Si substrate. After the deposition is completed, the photoresist is removed with acetone solution, the solvent is blown off by nitrogen gas, and then the electrode is dried. Finally, vacuum high-temperature annealing is performed. The conditions for high-temperature annealing are: annealing temperature of 150℃, atmosphere of Ar / N2 mixed gas, and annealing time of 50min, to obtain a self-powered polarization detector based on the B-HfTe5 / MoS2 / T-HfTe5 double heterojunction.
[0072] Example 7 Fabrication of a self-powered polarization detector based on a B-HfTe5 / MoSe2 / T-HfTe5 double heterojunction: S1. Remove B-HfTe5 material by mechanical peeling: Using B-HfTe5 single crystal as raw material, the single crystal is repeatedly peeled (5 times) with low-viscosity blue film tape and attached to SiO2 / Si substrate to obtain SiO2 / Si substrate with B-HfTe5 layer. The B-HfTe5 layer has a thickness of 118 nm, a width of 2 μm, and a length of 68 μm; S2. PVA solution (concentration of 4wt%) is dropped onto a polydimethylsiloxane (PDMS) film that can cover the material. The film is then gently scraped flat with a glass slide and dried at 55°C for 10 min to obtain a cured PVA film. The film is then placed on a clean glass slide. S3. MoSe2 is removed by mechanical peeling: MoSe2 single crystal is used as raw material, and the single crystal is repeatedly peeled (3-5 times) with low-tack blue film tape and attached to the PVA film to obtain a PVA film with MoSe2 layer. The MoSe2 layer has a thickness of 60 nm, a width of 15 μm, and a length of 50 μm. S4. Place the SiO2 / Si substrate with the B-HfTe5 layer on the sample stage of the transfer stage, fix the PVA film with the MoSe2 layer in the slot of the transfer stage, observe the overlapping part through the microscope of the transfer stage, select a suitable junction region, and gradually attach the two by controlling the transfer platform. Heat at 95℃ for 3 min, then remove and soak in 55℃ deionized water for 15 min. After removal, remove the PVA film on the surface, blow off the solvent with nitrogen gas and dry to obtain the SiO2 / Si substrate with the B-HfTe5 / MoSe2 van der Waals heterojunction. The B-HfTe5 layer and the MoSe2 layer are not completely overlapped, but have a misaligned structure. The areas of the two layers other than the overlapping parts are exposed with lengths of 28 μm and 15 μm respectively. The exposed area of the MoSe2 layer is referred to as the MoSe2 region. S5. Add PVA solution (concentration of 4wt%) to a polydimethylsiloxane (PDMS) film that can cover the material, scrape it flat with a glass slide, dry it at 55°C for 10 min to obtain a cured PVA film, and place it on a clean glass slide. S6. T-HfTe5 is removed by mechanical peeling: Using T-HfTe5 single crystal as raw material, the single crystal is repeatedly peeled (5 times) with low-adhesion blue film tape and attached to the PVA film to obtain a PVA film with T-HfTe5 layer. The T-HfTe5 layer has a thickness of 126 nm, a width of 2.3 μm, and a length of 63 μm; S7. Place the SiO2 / Si substrate with B-HfTe5 / MoSe2 van der Waals heterojunction on the sample stage of the transfer stage. Fix the PVA film with T-HfTe5 layer 5 in the slot of the transfer stage. Observe the overlapping part through the microscope of the transfer stage, select a suitable junction area, and gradually attach the two by controlling the transfer platform. Heat at 95℃ for 3 min, then remove and soak in 55℃ deionized water for 15 min. After removal, remove the PVA film on the surface, blow off the solvent with nitrogen gas and dry to obtain the SiO2 / Si substrate with B-HfTe5 / MoSe2 / T-HfTe5 van der Waals heterojunction. The T-HfTe5 layer and the B-HfTe5 layer are stacked in such a way that the substrates completely overlap. The exposed areas of the B-HfTe5 layer and the exposed areas of the T-HfTe5 layer have the same length in the vertical direction. Due to the van der Waals forces between the two layers, which are similar to the structural forces between intrinsic layers of the material, even if the B-HfTe5 layer is not exposed, it can still be regarded as a whole. The region where B-HfTe5, MoSe2, and T-HfTe5 layers overlap is denoted as the B-HfTe5 / MoSe2 / T-HfTe5 region; the region where B-HfTe5 and T-HfTe5 layers overlap is denoted as the B-HfTe5 / T-HfTe5 region. S8. A spin coater was used to spin-coat a SiO2 / Si substrate with a B-HfTe5 / MoSe2 / T-HfTe5 van der Waals heterojunction. The substrate was then heated at 105℃ for 4 min. Electron beam lithography was then used to precisely position and expose the electrode pattern. The exposed heterojunction was then developed with a developer, fixed with deionized water, and dried after the solvent was removed by a nitrogen stream to obtain the photolithographic heterojunction. The exposure and development parameters were as follows: the scanning speed of the lithography machine was 0.9 mm / s, the power was 28 mW, the developer was a 6 wt% tetramethylammonium hydroxide aqueous solution, and the development time was 18 s. S9. Metal is deposited on the heterojunction after photolithography to form drain and source electrodes. Simultaneously, part of the source electrode is located on the surface of the T-HfTe5 / B-HfTe5 region, and the other part is located on the surface of the SiO2 / Si substrate. Similarly, part of the drain electrode is located on the surface of the MoSe2 region, and the other part is located on the surface of the SiO2 / Si substrate. After the deposition is completed, the photoresist is removed with acetone solution, the solvent is blown off by nitrogen gas, and then the device is dried. Finally, it is subjected to vacuum high-temperature annealing. The conditions for high-temperature annealing are: annealing temperature of 150℃, atmosphere of Ar / N2 mixed gas, and annealing time of 50 min, to obtain a self-powered polarization detector based on the B-HfTe5 / MoSe2 / T-HfTe5 double heterojunction.
[0073] Comparative Example 1 (compared to Example 1, the T-HfTe5 layer is omitted) Fabrication of a self-powered polarization detector based on a B-HfTe5 / WS2 heterojunction: S1. Remove B-HfTe5 material using mechanical peeling method: Using HfTe5 single crystal as raw material, the single crystal is repeatedly peeled (5 times) using low-viscosity blue film tape and adhered to SiO2 / Si substrate to obtain SiO2 / Si substrate with B-HfTe5 layer. The B-HfTe5 layer has a thickness of 119 nm, a width of 2 μm, and a length of 80 μm; S2. PVA solution (concentration of 4wt%) is dropped onto a polydimethylsiloxane (PDMS) film that can cover the material. The film is then gently scraped flat with a glass slide and dried at 55°C for 10 min to obtain a cured PVA film. The film is then placed on a clean glass slide. S3. Remove WS2 using mechanical peeling method: Using WS2 single crystal as raw material, repeatedly peel (5 times) the single crystal with low-adhesion blue film tape and stick it on the PVA film to obtain a PVA film with WS2 layer. The WS2 layer has a thickness of 71 nm, a width of 8 μm, and a length of 31 μm; S4. Place the SiO2 / Si substrate with the B-HfTe5 layer on the sample stage of the transfer stage, fix the PVA film with the WS2 layer in the slot of the transfer stage, observe the overlapping part through the microscope of the transfer stage, select a suitable junction area, and gradually attach the two by controlling the transfer platform. Heat at 95℃ for 3 min, then remove and soak in 55℃ deionized water for 15 min. After removal, remove the PVA film on the surface, blow off the solvent with nitrogen gas and dry to obtain the SiO2 / Si substrate with the B-HfTe5 / WS2 van der Waals heterojunction. The B-HfTe5 layer and the WS2 layer are not completely overlapped, but have a staggered structure. The areas of the two layers other than the overlapping parts are exposed with lengths of 50 μm and 15 μm respectively. The exposed area of the WS2 layer is referred to as the WS2 region. S5. A spin coater was used to spin-coat a SiO2 / Si substrate with a B-HfTe5 / WS2 van der Waals heterojunction. The substrate was then heated at 95°C for 3 min. Electron beam lithography was then used to precisely position and expose the electrode pattern. The exposed heterojunction was then developed with a developer, fixed with deionized water, and dried after the solvent was removed by a nitrogen stream to obtain the photolithographic heterojunction. The exposure and development parameters were as follows: the scanning speed of the lithography machine was 0.9 mm / s, the power was 28 mW, the developer was a 6 wt% tetramethylammonium hydroxide aqueous solution, and the development time was 18 s. S9. Metal is deposited on the heterojunction after photolithography to form drain and source electrodes. Simultaneously, part of the source electrode is located on the surface of the B-HfTe5 region, and the other part is located on the surface of the SiO2 / Si substrate. Similarly, part of the drain electrode is located on the surface of the WS2 region, and the other part is located on the surface of the SiO2 / Si substrate. After the deposition is completed, the photoresist is removed with acetone solution, the solvent is blown off by nitrogen gas, and then the device is dried. Finally, it is subjected to vacuum high-temperature annealing. The conditions for high-temperature annealing are: annealing temperature of 150℃, atmosphere of Ar / N2 mixed gas, and annealing time of 50 min, to obtain a self-powered polarization detector based on the B-HfTe5 / WS2 heterojunction.
[0074] Comparative Example 2 (compared to Example 1, the B-HfTe5 layer is omitted) Fabrication of a self-powered polarization detector based on a T-HfTe5 / WS2 heterojunction: S1. Remove WS2 material using mechanical peeling method: Using WS2 single crystal as raw material, use low-viscosity blue film tape to repeatedly peel (5 times) the single crystal and stick it on SiO2 / Si substrate to obtain SiO2 / Si substrate with WS2 layer. The WS2 layer has a thickness of 15 nm, a width of 10 μm, and a length of 35 μm; S2. PVA solution (concentration of 4wt%) is dropped onto a polydimethylsiloxane (PDMS) film that can cover the material. The film is then gently scraped flat with a glass slide and dried at 55°C for 10 min to obtain a cured PVA film. The film is then placed on a clean glass slide. S3. T-HfTe5 is removed by mechanical peeling: Using HfTe5 single crystal as raw material, the single crystal is repeatedly peeled (5 times) with low-adhesion blue film tape and attached to the PVA film to obtain a PVA film with T-HfTe5 layer. The T-HfTe5 layer has a thickness of 135 nm, a width of 2 μm, and a length of 45 μm; S4. Place the SiO2 / Si substrate with the WS2 layer on the sample stage of the transfer stage. Fix the PVA film with the T-HfTe5 layer in the slot of the transfer stage. Observe the overlapping part through the microscope of the transfer stage, select a suitable junction area, and gradually attach the two by controlling the transfer platform. Heat at 95℃ for 3 min, then remove and soak in 55℃ deionized water for 15 min. After removal, remove the PVA film on the surface, blow off the solvent with nitrogen gas and dry to obtain the SiO2 / Si substrate with T-HfTe5 / WS2 van der Waals heterojunction. The T-HfTe5 layer and the WS2 layer are not completely overlapped, but have a misaligned structure. The areas of the two layers other than the overlapping parts are exposed with lengths of 23 μm and 18 μm respectively. The exposed area of the WS2 layer is referred to as the WS2 region. S5. A spin coater was used to spin-coat a SiO2 / Si substrate with a T-HfTe5 / WS2 van der Waals heterojunction. The substrate was then heated at 105℃ for 4 min. Electron beam lithography was then used to precisely position and expose the electrode pattern. The exposed heterojunction was then developed with a developer, fixed with deionized water, and dried after the solvent was removed by a nitrogen stream to obtain the photolithographic heterojunction. The exposure and development parameters were as follows: the scanning speed of the lithography machine was 0.9 mm / s, the power was 28 mW, the developer was a 6 wt% tetramethylammonium hydroxide aqueous solution, and the development time was 18 s. S9. Metal is deposited on the heterojunction after photolithography to form drain and source electrodes. At the same time, part of the source electrode is located on the surface of the T-HfTe5 region and the other part is located on the surface of the SiO2 / Si substrate. Similarly, part of the drain electrode is located on the surface of the WS2 region and the other part is located on the surface of the SiO2 / Si substrate. After the deposition is completed, the photoresist is removed with acetone solution, the solvent is blown off by nitrogen gas and then dried. Finally, vacuum high-temperature annealing is performed. The conditions for high-temperature annealing are: annealing temperature of 150℃, atmosphere of Ar / N2 mixed gas, and annealing time of 50 min, to obtain a self-powered polarization detector based on the T-HfTe5 / WS2 heterojunction.
[0075] Test case Figure 1 This is a schematic diagram of the structure of the self-powered polarization detector based on the B-HfTe5 / WS2 / T-HfTe5 double heterojunction in Example 1.
[0076] Figure 1 In the diagram, (S) is the source electrode and (D) is the drain electrode.
[0077] Figure 2 This is a schematic diagram of the internal depletion region of a self-powered polarization detector based on a B-HfTe5 / TMD / T-HfTe5 double heterojunction. It can be seen that this self-powered polarization detector, through the combined action of the upper and lower double heterojunctions, can completely deplete the intermediate TMD layer.
[0078] Figure 3 This document describes the structural and photoelectric performance characterization of a self-powered polarization detector based on a B-HfTe5 / WS2 / T-HfTe5 double heterojunction as described in Example 1. (a) is an optical microscope image of the fabricated device; (b) are Raman spectra recorded from the individual WS2 region, B-HfTe5 / T-HfTe5 region, and B-HfTe5 / WS2 / T-HfTe5 region; (c) are IV characteristic curves under 405 nm illumination at different optical power densities; and (d) V... dsThe time-resolved optical response diagram at 0 V and 405 nm illumination as a function of increasing light intensity is shown. The optical microscope image of the fabricated device reveals a classic three-electrode configuration: electrodes P1 and P2 are used to characterize the photoelectric properties of the B-HfTe5 / WS2 / T-HfTe5 device, while P2 and P3 are used together for in-situ characterization of the WS2 device. In the Raman spectrum, the WS2 spectrum exhibits its characteristic... (352 cm) -1 ) and A 1g (420 cm) -1 The model showed no displacement of the Raman peak in the overlapping region, which verifies the high-quality construction of the heterostructure. Figure 3 The curve c shows the current-voltage (IV) characteristics measured under dark and light conditions, further confirming the broadband photodetector capability, while the leftward shift of the curve under light highlights the obvious photovoltaic effect. Figure 3 The d-values show that the transient photoresponse under zero bias exhibits ultra-low dark current and excellent photosensitivity, with a dark current of only 0.78 pA and a value of 0.023 mW / cm². 2 With an on / off ratio as high as 14 at (405 nm) optical power, it demonstrates its excellent optoelectronic performance in self-powered mode.
[0079] Figure 4 The figure shows the polarization photoresponse of the self-powered polarization detector based on the B-HfTe5 / WS2 / T-HfTe5 double heterojunction in Example 1. (a) is a schematic diagram of the polarization-resolved photoresponse measurement device; (b) shows the self-powered time-resolved photocurrent at different polarization angles under 635 nm illumination; and (c) is a polar plot showing the relationship between photocurrent and polarization angle, displaying experimental data and fitting curves. As can be seen from the figure, Figure 4 A shows a schematic diagram of a polarization-resolved optical response measurement device, which is generated by passing a circularly polarized laser through a polarizer to produce linearly polarized light that is incident on the device. Figure 4 Figure b shows the time-resolved optical response curves at different polarization angles under 635 nm laser illumination. Although the incident laser power remains almost constant during polarizer rotation, the photocurrent exhibits significant periodic modulation. Figure 4 c shows the dependence of photocurrent on polarization angle, and the polarization anisotropy ratio (AR=I) at a wavelength of 405 nm. max / I min The value reached 6.73.
[0080] Figure 5This document describes the structural and photoelectric performance characterization of the self-powered polarization detector based on a B-HfTe5 / WSe2 / T-HfTe5 double heterojunction in Example 5. (a) is an optical microscope image of the fabricated device; (b) shows the IV characteristics under 405 nm illumination at different power densities; (c) shows the self-powered time-resolved photocurrent at different polarization angles under 405 nm illumination; and (d) is a polar plot showing the relationship between photocurrent and polarization angle, displaying experimental data and fitting curves. Figure 5 As can be seen from a, the optical microscope images of the fabricated device show that part of the source electrode is located on the surface of the T-HfTe5 / B-HfTe5 material, and part of the drain electrode is located on the surface of the WSe2 material. Figure 5 Figure b shows the current-voltage (IV) characteristics measured under both dark and light conditions, further confirming the broadband photodetector capability, while the curve shifts to the left under light conditions, highlighting the significant photovoltaic effect. Figure 5 Figure c shows the time-resolved optical response curves at different polarization angles under 405nm laser illumination. Although the incident laser power remains almost constant during polarizer rotation, the photocurrent exhibits significant periodic modulation. Figure 5 The d-value shows the dependence of photocurrent on polarization angle, and the polarization anisotropy ratio (AR=I) at a wavelength of 405 nm. max / I min It reached 5.01.
[0081] Figure 6 The structure and photoelectric performance of the self-powered polarization detector based on the B-HfTe5 / MoS2 / T-HfTe5 double heterojunction in Example 6 are characterized. (a) is an optical microscope image of the fabricated device, (b) is the IV characteristics under 405 nm illumination at different optical power densities, (c) is the self-powered time-resolved photocurrent at different polarization angles under 405 nm illumination, and (d) is a polar coordinate graph showing the relationship between photocurrent and polarization angle, displaying experimental data and fitting curves. As shown in Figure a, the optical microscope image of the fabricated device reveals a classic three-electrode configuration, with part of the source electrode located on the surface of the T-HfTe5 / B-HfTe5 material and part of the drain electrode located on the surface of the MoS2 material. Figure b shows the current-voltage (IV) characteristics measured under dark and illuminated conditions, further confirming the broadband photodetector capability. The curve shifts to the left under illumination, highlighting a significant photovoltaic effect. Figure c shows the time-resolved optical response curves at different polarization angles under 405 nm laser illumination. Although the incident laser power remains almost constant during polarizer rotation, the photocurrent exhibits significant periodic modulation. Figure d shows the dependence of the photocurrent on the polarization angle, with the polarization anisotropy ratio (AR=I) at 405 nm wavelength. max / I min It reached 3.26.
[0082] Figure 7 The structure and photoelectric performance of the self-powered polarization detector based on the B-HfTe5 / MoSe2 / T-HfTe5 double heterojunction in Example 7 are characterized. (a) is an optical microscope image of the fabricated device, (b) is the IV characteristics under 405 nm illumination at different optical power densities, (c) is the self-powered time-resolved photocurrent at different polarization angles under 405 nm illumination, and (d) is a polar coordinate graph showing the relationship between photocurrent and polarization angle, displaying experimental data and fitting curves. As shown in Figure a, the optical microscope image of the fabricated device reveals a classic three-electrode configuration, with part of the source electrode located on the surface of the T-HfTe5 / B-HfTe5 material and part of the drain electrode located on the surface of the MoSe2 material. Figure b shows the current-voltage (IV) characteristics measured under dark and illuminated conditions, further confirming the broadband photodetector capability. The curve shifts to the left under illumination, highlighting the significant photovoltaic effect. Figure c shows the time-resolved optical response curves at different polarization angles under 405 nm laser illumination. Although the incident laser power remains almost constant during polarizer rotation, the photocurrent exhibits significant periodic modulation. Figure d shows the dependence of the photocurrent on the polarization angle, with the polarization anisotropy ratio (AR=I) at 405 nm wavelength. max / I min It reached 3.55.
[0083] Figure 8 This image shows simulated polarization imaging at different angles (0°, 30°, 60°, 90°) using an imaging system based on a B-HfTe5 / WS2 / T-HfTe5 double heterojunction polarization detector, as described in Example 4. The figure illustrates the polarization angle-dependent imaging test results under 635 nm laser illumination. High-resolution images of "beautiful," "good," "life," and "liveliness" were successfully obtained. By modulating the polarization angle, a clear difference in photocurrent between patterns was achieved. Complete and clear imaging was completed at polarization angles of 0°, 30°, 60°, and 90°, demonstrating the powerful polarization imaging capabilities of the B-HfTe5 / WS2 / T-HfTe5 device.
[0084] Figure 9For Comparative Example 1, the structure and polarization photoelectric performance of the self-powered polarized light detector based on the B-HfTe5 / WS2 heterojunction are characterized. (a) is an optical microscope image of the fabricated device; (b) shows the self-powered time-resolved photocurrent at different polarization angles under 405 nm illumination; and (c) is a polar plot showing the relationship between photocurrent and polarization angle, displaying experimental data and fitting curves. Figure a shows that the optical microscope image of the fabricated device uses a classic three-electrode configuration, with some source electrodes located on the surface of the B-HfTe5 material and some drain electrodes located on the surface of the WS2 material. Figure b shows the time-resolved optical response curves at different polarization angles under 405 nm laser illumination. Although the incident laser power remains almost constant during polarizer rotation, the photocurrent exhibits significant periodic modulation. Figure c shows the dependence of the photocurrent on the polarization angle, with the polarization anisotropy ratio (AR=I) at 405 nm wavelength. max / I min It reached 3.44.
[0085] Figure 10 For Comparative Example 2, the structure and polarization photoelectric performance of the self-powered polarized light detector based on the T-HfTe5 / WS2 heterojunction are characterized. (a) is an optical microscope image of the fabricated device; (b) shows the self-powered time-resolved photocurrent at different polarization angles under 405 nm illumination; and (c) is a polar plot of the photocurrent versus polarization angle, displaying experimental data and fitting curves. As shown in the figures, the optical microscope image of the fabricated device shows a classic three-electrode configuration, with some source electrodes located on the surface of the B-HfTe5 material and some drain electrodes located on the surface of the WS2 material. Figure b shows the time-resolved optical response curves at different polarization angles under 405 nm laser illumination. Although the incident laser power remains almost constant during polarizer rotation, the photocurrent exhibits significant periodic modulation. Figure c shows the dependence of the photocurrent on the polarization angle, with the polarization anisotropy ratio (AR=I) at 405 nm wavelength. max / I min It reached 1.31.
[0086] Figure 11 This document compares the performance of the self-powered polarization detector based on the B-HfTe5 / WS2 / T-HfTe5 double heterojunction in Example 1 with the self-powered polarization detector based on the B-HfTe5 / WS2 heterojunction in Comparative Example 1 and the self-powered polarization detector based on the T-HfTe5 / WS2 heterojunction in Comparative Example 2. In Example 1, (a) is a comparison of responsivity (R) and specific detectivity (D*), and in Example 2, (b) is a comparison of polarization anisotropy ratio (AR).
[0087] Figure 11 In (a), the dark bars represent R, and the light bars represent D*.
[0088] As can be seen from the figure, the self-powered polarization detector of the B-HfTe5 / WS2 / T-HfTe5 double heterojunction in Example 1 is superior to the single heterojunction in Comparative Examples 1-2 in terms of R, D* and AR, which fully demonstrates the enhancement effect of the double heterojunction.
[0089] Comparative Example 3 (Mirror Structure) The only difference from Example 1 is that the types of single-crystal materials stripped in steps S1, S3, and S6 are replaced with WS2 single crystals, HfTe5 single crystals, and WS2 single crystals, respectively. The resulting product is denoted as WS2 / HfTe5 / WS2.
[0090] Comparative Example 4 (Mirror Structure) The only difference from Example 5 is that the types of single-crystal materials stripped in steps S1, S3, and S6 are replaced with WSe2 single crystals, HfTe5 single crystals, and WSe2 single crystals, respectively. The resulting product is denoted as WSe2 / HfTe5 / WSe2.
[0091] Comparative Example 5 (Mirror Structure) The only difference from Example 6 is that the types of single-crystal materials stripped in steps S1, S3, and S6 are replaced with MoS2 single crystals, HfTe5 single crystals, and MoS2 single crystals, respectively. The resulting product is denoted as MoS2 / HfTe5 / MoS2.
[0092] Comparative Example 6 (Mirror Structure) The only difference from Example 7 is that the types of single-crystal materials stripped in steps S1, S3, and S6 are replaced with MoSe2 single crystals, HfTe5 single crystals, and MoSe2 single crystals, respectively. The resulting product is denoted as MoSe2 / HfTe5 / MoSe2.
[0093] Figure 12The figures show an AR comparison of the self-powered polarization detector based on a B-HfTe5 / WS2 / T-HfTe5 double heterojunction in Example 1, the self-powered polarization detector based on a B-HfTe5 / WSe2 / T-HfTe5 double heterojunction in Example 5, the self-powered polarization detector based on a B-HfTe5 / MoS2 / T-HfTe5 double heterojunction in Example 6, and the self-powered polarization detector based on a B-HfTe5 / MoSe2 / T-HfTe5 double heterojunction in Example 7, with the corresponding mirror-image structure devices of Comparative Examples 3-6. As can be seen from the figures, the outer HfTe5 layer exhibits a stronger polarization anisotropy ratio than the inner layer.
[0094] Figure 13 The data presented in Example 1, based on a B-HfTe5 / WS2 / T-HfTe5 double heterojunction, show the polarization response data obtained from in-situ testing of the WS2 region. (a) shows the self-powered time-resolved photocurrent at different polarization angles under 405 nm illumination, and (b) is a polar plot of the photocurrent versus polarization angle, displaying the experimental data and fitted curves. The figures show that the photocurrent generated by the WS2 device is not significantly dependent on the polarization angle, confirming the full contribution of HfTe5 to the polarization selection function of the B-HfTe5 / WS2 / T-HfTe5 double heterojunction device.
[0095] The performance of the self-powered polarization detector of Example 1 was compared with that of WSe2 / Ta2NiSe3 / WSe2 in the prior art (DOI:10.1021 / acsami.3c04147).
[0096] Figure 14 This is a performance comparison chart of the self-powered polarization detector based on the B-HfTe5 / WS2 / T-HfTe5 double heterojunction in Example 1 and the WSe2 / Ta2NiSe3 / WSe2 in the prior art. As can be seen from the chart, the complete depletion effect brought about by the double heterojunction in the product of this invention results in a significant lead over the prior art in both R and D*.
[0097] Figure 14 In the diagram, dark bars represent R, and light bars represent D*.
[0098] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.
[0099] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A self-powered polarization detector based on a B-HfTe5 / TMD / T-HfTe5 double heterojunction, characterized in that, The self-powered polarization detector comprises, in a stacked manner, a silicon substrate, a B-HfTe5 layer, a TMD layer, and a T-HfTe5 layer arranged sequentially. The TMD layer, serving as a light absorption layer, is sandwiched between the B-HfTe5 layer and the T-HfTe5 layer, forming a B-HfTe5 / TMD / T-HfTe5 double heterojunction structure; The material of the TMD layer is tungsten disulfide, tungsten diselenide, molybdenum disulfide, or molybdenum diselenide. The thickness of the B-HfTe5 layer is 40-200 nm, the width is 1-10 μm, and the length is 30-100 μm; The TMD layer has a thickness of 40-100 nm, a width of 1-50 μm, and a length of 30-200 μm; The thickness of the T-HfTe5 layer is 40-300 nm, the width is 1-10 μm, and the length is 30-200 μm; The self-powered polarization detector also includes a first electrode and a second electrode; The silicon substrate is a Si / SiO2 substrate.
2. A method for fabricating a self-powered polarization detector based on a B-HfTe5 / TMD / T-HfTe5 double heterojunction as described in claim 1, characterized in that, Includes the following steps: B-HfTe5, TMD, and T-HfTe5 materials are sequentially stacked onto a silicon substrate using mechanical exfoliation and dry transfer to form a silicon substrate with a B-HfTe5 / TMD / T-HfTe5 dual heterojunction structure.
3. The preparation method according to claim 2, characterized in that, After forming the silicon substrate with the B-HfTe5 / TMD / T-HfTe5 double heterojunction structure, the following steps are also included: Electrode patterns are fabricated on the silicon substrate having a B-HfTe5 / TMD / T-HfTe5 double heterojunction structure by photolithography and development. Then, metal is deposited on the electrode patterns to form electrodes, and the substrate is annealed to obtain the self-powered polarization detector.
4. The application of the self-powered polarization detector based on B-HfTe5 / TMD / T-HfTe5 double heterojunction as described in claim 1 in the field of integrated optoelectronic devices.
5. A polarized light detection method, characterized in that, The self-powered polarization detector based on B-HfTe5 / TMD / T-HfTe5 double heterojunction as described in claim 1 is used to receive incident light, collect photocurrent signals under zero bias or low bias, and determine the polarization direction, polarization intensity or polarization state of the incident light based on the change of the photocurrent signal with the polarization angle of the incident light. The polarization angle of the incident light forms an angle with the crystal orientation of the HfTe5 nanosheets. θ Photocurrent signal follows θ It exhibits periodic changes.
6. A polarization imaging system, characterized in that, It includes the self-powered polarization detector, light source, polarization modulation module, scanning module, and signal acquisition module based on the B-HfTe5 / TMD / T-HfTe5 double heterojunction as described in claim 1.